An Analysis of Cultural Content in English Textbook “Pathway to English” for Grade X - Fasya, Redhata Ardian; Rahmawati, Maya; Fitriyana, Wahyudin (Peneliti.net, 2024)
This undergraduate thesis analyzes the cultural content within the English textbook “Pathway to English” designed for 10th-grade high school students, published by Erlangga in 2022. Employing a qualitative descriptive study approach, this research centers on the textbook materials, excluding exercise items. Data comprising text and images are categorized according to Cortazzi & Jin’s (1999) cultural categories and Moran’s (2001) cultural dimensions. The results of the analysis reveal that the Target Culture category and the “persons” dimension predominantly feature in the acquired data. These findings indicate the necessity for teachers to develop supplementary materials to cater to students’ needs in comprehending diverse cultures within the context of English as a Foreign Language (EFL). As a result, students can be exposed to a more comprehensive and profound learning experience, potentially enhancing their understanding of global cultural diversity.